Effect of tenofovir containing ART on renal function in patients with moderate/severe reduced creatinine clearance at baseline: A retrospective study at two referral hospitals in Namibia - Francis Kalemeera; Brian Godman; Andy Stergachis; Tim Rennie (Wiley, 2023)
Abstract Prescription of tenofovir disoproxil fumarate (TDF) for patients with baseline creatinine clearances (CrCl) <60 mL/min is said to increase risk of further decline in CrCl. Study objectives were to assess incidence of improvement and predictors thereof; to assess incidence of decline and transition to lower stages of CrCl; and comparison of declines between patients with a baseline CrCl < 60mL/min (group‐I) and ≥ 60 mL/min (group‐II). The study was retrospective, included patients 16 yrs or older who received TDF‐containing ART. Improvement and decline were defined as ≥ 25% increase or decrease in CrCl, respectively. Binary logistic regression was performed to identify predictors of improvement. Groups I and II had 2862 and 7526 patients, respectively. In group‐I, improvement in CrCl was observed in 40.1% (n = 1146), and was associated with stage IV of CrCl (adjusted Odds Ratio [aOR]=13.4 [95% CI: 6.7 ‐ 26.9, P < .001]); male gender (aHR = 1.8 [95% CI: 1.5 ‐ 2.2, P < .001]); and a poor HIV‐status (aHR = 1.2 [95% CI: 1.0 ‐ 1.4], P = .033). In group‐I and group‐II, respectively, decline occurred in 2.3% and 13.0%, (P < .001); transition to lower stages occurred in 1.0% and 25.2% (P < .001); and migration to stage IV CrCl occurred in 1.0% and 0.5% (P < .001). Improvement was more likely than decline in group‐I patients. Although, group‐I patients were more likely to experience new onset severe reduced CrCl than group‐II patients, the proportions were extremely low. TDF should not be withheld from HIV‐positive patients with a baseline CrCl < 60 mL/min.